2015
DOI: 10.1074/jbc.m115.670182
|View full text |Cite
|
Sign up to set email alerts
|

Vibrio cholerae Porin OmpU Induces Caspase-independent Programmed Cell Death upon Translocation to the Host Cell Mitochondria

Abstract: Porins, a major class of outer membrane proteins in Gramnegative bacteria, primarily act as transport channels. OmpU is one of the major porins of human pathogen, Vibrio cholerae. In the present study, we show that V. cholerae OmpU has the ability to induce target cell death. Although OmpU-mediated cell death shows some characteristics of apoptosis, such as flipping of phosphatidylserine in the membrane as well as cell size shrinkage and increased cell granularity, it does not show the caspase-3 activation and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 69 publications
(81 reference statements)
3
26
0
Order By: Relevance
“…****, P Ͻ 0.0001; ns, not significant. (38). The binding and internalization of V. fischeri OMV by squid hemocytes and epithelial cells have been recently demonstrated (10), and future work will aim to determine the mechanism underlying the connection between the OmpU of OMVs and these host responses.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…****, P Ͻ 0.0001; ns, not significant. (38). The binding and internalization of V. fischeri OMV by squid hemocytes and epithelial cells have been recently demonstrated (10), and future work will aim to determine the mechanism underlying the connection between the OmpU of OMVs and these host responses.…”
Section: Discussionmentioning
confidence: 94%
“…Similarly, OmpU, the major OMP of Vibrio spp., plays roles in both pathogenesis and symbiosis within this genus (6,34). For instance, in pathogenic relationships, OmpU facilitates colonization (35), allowing binding to host tissue and inducing specific immune responses, including cell death (36)(37)(38). Conversely, in the mutualistic V. fischeri, although an ompU mutant has no growth defect in culture, it is only 60% as effective in the colonization process (39) and is compromised in the ability to avoid phagocytosis by the host's hemocytes (40), indicating a role for this OMP in the normal establishment and persistence of symbiosis.…”
Section: Discussionmentioning
confidence: 99%
“…Different bacterial proteins can induce a number of host cellular responses, and cell death is one of them. A study on V. cholerae porin OmpU suggested that it has the ability to induce target cell death (Gupta et al, 2015). Recently, a group reported that outer membrane vesicle associated biologically active proteases from V. cholerae can induce cytotoxic and inflammatory response in host cells (Mondal et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Cells were also imaged by fluorescence microscope (Zeiss) after immunostaining of actin cytoskeleton using anti-actin primary antibody and AlexaFluor 488-conjugated secondary antibody followed by counterstaining with 4', 6-diamidino-2-phenylindole (DAPI). Alterations in cell size and complexity in GbpA-treated cells were examined by flow cytometer under the parameters applicable for forward scattering (FSC) and side scattering (SSC), as described previously (Gupta et al, 2015). Here, FSC correlates with the measure of cell size and shape, whereas SSC indicates relative cell granularity, refractivity and presence of intra-cellular structures that can reflect the light.…”
Section: Methodsmentioning
confidence: 99%
“…OmpU is an outer-membrane protein common among various Vibrio species. It is mainly porin in nature, but several studies have reported that OmpU plays other roles ranging from helping bacteria for survival and pathogenesis to modulation of host-immune responses and target cell death (29)(30)(31)(32)(33). Earlier studies from our laboratory have shown that Vibrio cholerae OmpU can translocate to host cell mitochondria and induce programmed cell death.…”
mentioning
confidence: 99%